From single-molecule precursors to coupled Ag2S/TiO2 nanocomposites - Neves, Márcia C. (2008)
A single-source approach using mild temperatures was applied to prepare morphological well-defined and coupled TiO2/metal–sulfide nanocomposites. Metal N-alkyldithiocarbamates were used as the precursors to the metal–sulfide nanophases and, in particular, Ag2S nanostructures were investigated in more detail. These were observed as nanoislands at the surface of TiO2 (anatase) particles, which were used as substrates. To explain the formation of these nanocomposite particulates, a tentative mechanism has been pro- Introduction In recent years, the rational design of functional materials using moderate reaction conditions has been a general trend in materials chemistry.[1] In fact, this corresponds to a new paradigm in materials science in which, depending on the applications of the materials, their final properties can be tailored from the synthesis. In this sense, controlling the morphology of particulates appears to be obvious requirement to control size-dependent functionalities. A clear example of this trend is the high degree of control over the optical properties of semiconductor nanocrystals whose unique size-dependent behaviour can be tuned during the synthesis. Applications which rely on the size tunability of semiconductor nanocrystals have already been developed, such as in photoluminescent biotags and electroluminescence devices.[1] Another important application envisaged for semiconducting nanoparticles is their use in photocatalytic processes with relevance for environmental decontamination.[2] The most investigated systems rely on TiO2 photocatalysts, that can be coupled to a visible sensitizer which may be a metal complex, a dye or a second semiconducting nano- [a] Department of Chemistry, CICECO, University of Aveiro, 3810-193 Aveiro, Portugal Fax: +351-234-370-084 E-mail: tito@ua.pt [b] Department of Chemistry and Biochemistry, CCMM, University of Lisbon, Campo Grande, Ed. C8, 1749-016 Lisboa, Portugal [c] Physical Chemistry, Saarland University, 66123 Saarbrücken, Germany [d] Department of Chemistry, QOPNA, University of Aveiro, 3810-193 Aveiro, Portugal Supporting information for this article is available on the WWW under http://www.eurjic.org or from the author. © 2008 Wiley-VCH Verlag 4380 GmbH & Co. KGaA, Weinheim Eur. J. Inorg. Chem. 2008, 4380–4386 posed which involves the controlled release of sulfide ions from an intermediate coordination compound. Because the growth of the metal sulfide can be controlled at the surface of a photoactive substrate, we anticipate the potential of this synthetic method to chemical design reasonable amounts of semiconductor-sensitized TiO2, such as Ag2S/TiO2 nanocomposites.